Struktur Komunitas Fitoplankton Di Perairan Morosari Kecamatan Sayung Kabupaten Demak - Fajrina, Hilyati; Endrawati, Hadi; Zainuri, Muhammad (977-2407769)
Morosari waters located in Sayung District, Demak Regency is waters area where there is a mixture of land and sea water. Settlement activity, aquaculture, industrial land and existing at the entry and exit activities of fishing boats around the estuary can contribute to the dynamics of water quality fluctuations and productivity. The dynamics of water quality that occur greatly affect community structure and distribution of phytoplankton in the waters. The results of this study showed 28 genera for the vertical method, while for the method of horizontally obtained 31 genera. Average abundance obtained by the observation station was 1087.09 cells/l with vertical method, while for the horizontal method obtained 884.69 cells/l. While the abundances obtained by times of sampling average of 1087.09 cells/l for the vertical method, while for the horizontal method was 831.38 cells/l. Index phytoplankton diversity showed medium and obtained the average gain by the station is 2.02 for method of vertical and horizontally method to obtain 1.85. While based on the sampling time obtained an average of 2.09 for the vertical method, and for the horizontal method is 1.58. Uniformity index indicates the type of high uniformity and obtained the average by the station is 0.68 for the vertical method, while the horizontal method is obtained 0.4. While the sampling time is obtained based average of 0.64 for the vertical method, while for the horizontal method is 0.51. Dominance index obtained average based on the observation station is 0.3 for the vertical method, while the horizontal method obtained 0.6. While the sampling time is obtained based on an average of 0.35 for the vertical method, where for the horizontal method is 0.48 which indicates there is no dominating genus.